A Comparison of Insufficient Effort Rates, Neuropsychological Functioning, and Neuropsychiatric Symptom Reporting in Military Veterans and Civilians with Chronic Traumatic Brain Injury. (30th September 2013) - Gfeller, Jeffrey D.; Roskos, P. Tyler; Granacher, Robert P.; Sweet, Jerry J.; Felthous, Alan R.
<x xml:space="preserve">Abstract</x> Neuropsychological evaluation of persons with chronic traumatic brain injury (TBI) symptoms is complicated by multiple factors. The authors explored the impact of mechanism of injury, effort testing performance, and neuropsychiatric status in a sample of military veterans (V‐TBI) and civilians (C‐TBI) with chronic TBI. V‐TBI (n = 74), C‐TBI (n = 67), and healthy civilian control (C‐HC) participants (n = 66), completed a battery of neuropsychological, effort, and self‐report neuropsychiatric measures. Results indicated that C‐HC and C‐TBI participants exhibited comparably low failure rates on effort tests (6% and 3%, respectively). V‐TBI participants exhibited significantly higher rates of failure (18%). Subgroups (n = 20) of effort‐screened participants matched for demographics and disability level were compared regarding neuropsychological performance and neuropsychiatric self‐report. Both TBI groups exhibited limited neuropsychological impairment, relative to the C‐HC participants. The V‐TBI group exhibited pronounced neuropsychiatric symptomology compared with the other participant groups. The implications of these findings are discussed for evaluation in the context of disability and litigation. Copyright © 2013 John Wiley & Sons, Ltd.